2018
DOI: 10.1021/acs.inorgchem.8b01603
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Separation and Recovery of Uranium from Mixture of Uranium(VI) and Lanthanide(III) Ions in Aqueous Medium

Abstract: Separation of uranium (U) from interfering lanthanide ions (Ln) in aqueous medium is important in view of sustainable nuclear power production and remediation of radioactive waste. Separation of U in aqueous medium by electrochemical means is still unexplored. Herein, we report electrochemical separation of U from interfering lanthanides ions in 0.1 M KCl on poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) modified platinum (PEDOT:PSS/Pt) electrode. U in solution commonly exists as uranyl (UO). U separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…This is presumably because the synthesized peptides are very expensive materials and cannot compete with bulk chemical substances employed in conventional separation processes. 4 The market price of uranium is too low to consider peptides as potential materials for uranium recovery, even though such a possibility exists. 5 A more promising application of uraniumpeptide interaction would be to use it in uranium-detecting sensors.…”
Section: Introductionmentioning
confidence: 99%
“…This is presumably because the synthesized peptides are very expensive materials and cannot compete with bulk chemical substances employed in conventional separation processes. 4 The market price of uranium is too low to consider peptides as potential materials for uranium recovery, even though such a possibility exists. 5 A more promising application of uraniumpeptide interaction would be to use it in uranium-detecting sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Thus, it is greatly important to remove and recycle uranium from aqueous solutions for environmental conservation, human health, and sustainable development of nuclear energy. [24,25] In the last few decades, various treatment techniques including biological treatments, [26] membrane treatment, [27,28] adsorption, [29][30][31][32] advance oxidation processes, [33] chemical precipitation processes, [34] ion exchange, [35][36][37] and electrochemical method [38][39][40] have been developed to uptake uranium from aqueous solutions. However, most of these methods have various drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because actinide (An) elements fill the 5f subshell, the physicochemical properties and redox behaviors of Ln and An ions are observed to be very similar . Because of their similarities and diverse oxidation states, efficient detection, separation, and recovery of an Ln (or An) element from mixed ions have been a challenging project without any interferences among them. …”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical redox behaviors of metal ions are also known to be highly dependent on concentration, pH, and temperature. Furthermore, the nature of an electrode is another important factor, and the redox potentials and their corresponding current densities are reported to be tailored by the modification of an electrode. , Agarwal and Sharma developed a platinum (Pt) electrode modified by poly­(3,4-ethylenedioxythiophene)-poly­(styrenesulfonate) and showed that the newly developed electrode could efficiently electrodeposit UO 2 without any interferences of La 3+ , Ce 3+ , and Sm 3+ ions in solution . Surface functionalization of an electrode has also been employed using Lewis basic N-containing ligands such as terpyridines. Dares et al developed a terpyridine-functionalized ITO electrode and controlled electrochemical oxidation of Am­(III) in a nitric acid solution for the selective separation of Am from Ln elements in nuclear wastes .…”
Section: Introductionmentioning
confidence: 99%